2000
DOI: 10.1002/1521-3765(20001201)6:23<4358::aid-chem4358>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoprolines (Pro) in Drug Design: Direct Insertion of Pro Systems into Cyclosporin C

Abstract: The insertion of acetals that exhibit variable structural features into complex peptides such as cyclosporin C (CsC) results in oxazolidine derivatives (pseudoprolines, psiPro) of tailored physico-chemical and biological properties. N,O-Acetalation of the 2-threonine hydroxyl group and the preceding amide nitrogen of CsC is achieved by treating the molecule with a number of both arylated and non-arylated dimethyl acetals. The psiPro-containing CsC derivatives exhibit enhanced conformational backbone rigidity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Despite the efficiency of this method, the synthesis of the corresponding dipeptide unit in solution, FmocXaaCys(W R,R' pro), is mandatory that prevents the generalization of the approach. More recently, the insertion of thiazolidine systems into Ser-peptides has been investigated [10,11]. But the procedure has only been proved on a dipeptide and in the case of the cyclosporine A analog the yield remains very low.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the efficiency of this method, the synthesis of the corresponding dipeptide unit in solution, FmocXaaCys(W R,R' pro), is mandatory that prevents the generalization of the approach. More recently, the insertion of thiazolidine systems into Ser-peptides has been investigated [10,11]. But the procedure has only been proved on a dipeptide and in the case of the cyclosporine A analog the yield remains very low.…”
Section: Introductionmentioning
confidence: 99%
“…The oxazole was then formed via cyclodehydration upon treatment with DAST and potassium carbonate, then subsequent oxidation using bromochloroform and DBU. 32,37,38 Coupling fragments 1 and 2, followed by peptide macrocyclization furnished the desired oxazole peptidomimetic derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…27,32 Further, triazoles induce a rigid conformation by mimicking trans amide bonds. 27,30 Studies have shown that a single N -methyl, D-aa or N -methyl D-aa play a critical role in locking the San A-amide macrocyclic analogs into a single conformation.…”
Section: Introductionmentioning
confidence: 99%
“…If L-proline increases affinity this will indicate the important role of a turn segment. Proline and other N-alkylated amino acids (8), (9) prevent the formation of α-helices as they do not contribute to hydrogen bonds but induce turn structures [93,94].…”
Section: Side-chain Modificationmentioning
confidence: 99%